Assessing the Diversity and Stability of Cellular Immunity Generated in Response to the Candidate Live-Attenuated Dengue Virus Vaccine TAK-003 - Waickman, Adam T.; Friberg, Heather; Gargulak, Morgan; Kong, Amanda; Polhemus, Mark; Endy, Timothy; Thomas, Stephen J.; Jarman, Richard G.; Currier, Jeffrey R. (Frontiers in Immunology, 2019)
The development of an efficacious DENV vaccine has been a long-standing public health priority. However, this effort has been complicated significantly due to the hazard presented by incomplete humoral immunity in mediating immune enhancement of infection and disease severity. Therefore, there is a significant need for DENV vaccine platforms capable of generating broad immune responses including durable cellular immunity, as well as novel analytical tools to assess the magnitude, diversity, and persistence of vaccine-elicited immunity. In this study, we demonstrate that the recombinant, tetravalent, live-attenuated DENV vaccine TAK-003 elicits potent and durable cellular immunity against both the structural and non-structural proteins of all four DENV serotypes, which is maintained for at least 4 months post-immunization. Although not contained within the vaccine formulation, significant reactivity against the non-structural (NS) proteins of DENV-1, -3 and -4 is observed following vaccination, in an extent directly proportional to the magnitude of responses to the corresponding vaccine components. Distinct, quantifiable, and durable patterns of DENV antigen reactivity can be observed in individuals following vaccination. Finally, detailed epitope mapping of T cell reactivity against the DENV-2 proteome using a matrix of overlapping peptide pools demonstrated that TAK-003 elicits a broad response directed across the DENV-2 proteome, with focused reactivity in NS1 and NS3. We conclude that, as measured by an IFN- ELISpot assay, a single dose of TAK-003 generates potent T cell-mediated immunity which is durable in magnitude and breadth through four months post-vaccination.